Enhancing Capacity of Community–Academic Partnerships to Achieve Health Equity: Results From the CBPR Partnership Academy. Issue 4 (July 2020) - Coombe, Chris M.; Schulz, Amy J.; Guluma, Lello; Allen, Alex J.; Gray, Carol; Brakefield-Caldwell, Wilma; Guzman, J. Ricardo; Lewis, Toby C.; Reyes, Angela G.; Rowe, Zachary; Pappas, Lisa A.; Israel, Barbara A.
Community-based participatory research (CBPR) is an equitable partnership approach that links academic researchers, community organizations, and public health practitioners to work together to understand and address health inequities. Although numerous educational materials on CBPR exist, few training programs develop the skills and knowledge needed to establish effective, equitable partnerships. Furthermore, there are few professional development opportunities for academic researchers, practitioners, and community members to obtain these competencies in an experiential co-learning process. In response, the Detroit Community–Academic Urban Research Center developed the CBPR Partnership Academy, an innovative, yearlong capacity-building program facilitated by experienced community and academic partners, involving an intensive short course, partnership development, grant proposal preparation and funding, mentoring, online learning forums, and networking. Three diverse cohorts (36 teams) from 18 states and 2 tribal nations have participated. We describe the rationale and components of the training program and present results from the first two cohorts. Evaluation results suggest enhanced competence and efficacy in conducting CBPR. Outcomes include partnerships established, grant proposals submitted and funded, workshops and research conducted, and findings disseminated. A community–academic partner-based, integrated, applied program can be effective for professional development and establishing innovative linkages between academics and practitioners aimed at achieving health equity.